2008
DOI: 10.1152/ajpendo.90460.2008
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity and fetal programming: effects of a high-carbohydrate nutritional modification in the immediate postnatal life of female rats

Abstract: Srinivasan M, Dodds C, Ghanim H, Gao T, Ross PJ, Browne RW, Dandona P, Patel MS. Maternal obesity and fetal programming: effects of a high-carbohydrate nutritional modification in the immediate postnatal life of female rats. Am J Physiol Endocrinol Metab 295: E895-E903, 2008. First published August 5, 2008 doi:10.1152/ajpendo.90460.2008.-Our earlier studies have shown that the artificial rearing of newborn rat pups [first generation high carbohydrate (1-HC)] on an HC milk formula resulted in chronic hyperinsu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 40 publications
3
38
0
1
Order By: Relevance
“…Therefore, expression of Pparg may be promoted by increases in NEFA and insulin levels in offspring. The milk composition also influences NEFA and insulin levels in offspring and is altered by a change in maternal diet (27). In this study, fat and energy in milk of HD-fed dams during lactation were very high compared with those in CDfed dams.…”
Section: Discussionmentioning
confidence: 55%
“…Therefore, expression of Pparg may be promoted by increases in NEFA and insulin levels in offspring. The milk composition also influences NEFA and insulin levels in offspring and is altered by a change in maternal diet (27). In this study, fat and energy in milk of HD-fed dams during lactation were very high compared with those in CDfed dams.…”
Section: Discussionmentioning
confidence: 55%
“…HC term fetuses were hyperinsulinemic and HC fetal islets secreted increasing amounts of insulin in the presence of glucose and amino acids [42] . Surprisingly, adaptations supporting hyperphagia were evident in the fetal HC hypothalamus [41] . Although during the suckling period plasma insulin levels in HC pups were similar to those of age-matched control pups (due most likely to a suppressive effect of high-fat/low-carbohydrate content of rat milk), immediately after weaning HC offspring developed hyperinsulinemia which persisted into adulthood.…”
Section: Patel/srinivasanmentioning
confidence: 91%
“…The HC intrauterine environment was characterized by hyperinsulinemia, hyperleptinemia, increased plasma levels of several proinflammatory markers and significantly increased body weight compared to control female pregnant rats. Embryo transfer experiments (mother-fed embryos to HC mother and vice versa) indicated that mere fetal development in the adverse intrauterine environment of the HC female rat was sufficient for fetal programming of the offspring [41] . Cross-breeding of HC female rats with normal and HC male rats and cross-fostering of HC offspring by control dams also supported the above observation [Vadlamudi and Patel, unpubl.…”
Section: Patel/srinivasanmentioning
confidence: 99%
“…Finally, while for the purposes of this review, we have focussed on animal studies reporting programming effects in the offspring as a consequence of exposure to maternal obesity/high calorie diet during pregnancy alone or during both pregnancy and lactation, the critical importance of nutrition in the early postnatal period has also been demonstrated in a number of animal models. Thus, in rats, offspring exposed to early postnatal overnutrition as a consequence of suckling by mothers on a high-fat diet, as a result of artificial feeding with a high-carbohydrate diet or as a result of rearing in small litters are at increased risk of obesity and cardiometabolic disease (Plagemann et al 1992, Srinivasan et al 2008. Importantly, such effects are also noted in other species including non-human primates, for example overfeeding in the pre-weaning period increases adiposity in female baboons in young adulthood (Lewis et al 1986).…”
Section: Timing Of Exposurementioning
confidence: 99%